Factors Affecting the Sustainability of Octopus Cracker MSMEs in Linau Village, Maje Sub-District, Kaur Regency - Dolly Madya Parton Manullang; Herri Fariadi; Ana Nurmalia (Utami Publisher, 2026)
Octopus crackers in Linau Village are an important part of the culinary culture of the people of Kaur Regency. This needs to be managed for business sustainability. This study aims to analyze the level of sustainability and factors affecting the sustainability of octopus cracker MSMEs in Linau Village, Maje District, Kaur Regency. The research method used was a survey method with a census sampling technique of 12 octopus cracker MSME actors. The data were analyzed descriptively to determine the level of sustainability and using multiple linear regression analysis to test the effect of independent variables on dependent variables. The results showed that the sustainability level of octopus cracker MSMEs in Linau Village was in the “very high” category with an average score of 83.73. The factors influencing the sustainability of octopus cracker MSMEs in Linau Village, Maje District, Kaur Regency were raw material availability (X1), product innovation (X2), production technology (X3), Market access (X5), Environmental awareness and sustainability (X6), while the business management variable (X4) has no effect on the sustainability of the octopus cracker business in Linau Village, Maje District, Kaur Regency.